FN1, FOS, and ITGA5 induce preeclampsia: Abnormal expression and methylation - Mei Zhao; Lin Li; Xiumei Yang; Jianying Cui; Hong Li (Taylor & Francis Group, 2017)
Objective: As a frequent hypertensive disorder in pregnancy, preeclampsia causes 15% of all preterm deliveries. This study aims to understand its mechanism via analyzing gene expression and methylation data. Methods: Human gene expression microarray data (GSE73374) and corresponding DNA methylation microarray data (GSE73375) of preeclamptic placental tissues (n = 19) and normotensive placental tissues (n = 17) were obtained from the Gene Expression Omnibus. Differentially expressed genes (DEGs), differentially methylated regions (DMRs) and CpG islands (DMIs) were identified and compared. Pathway enrichment analysis was performed, and the functional interactions were investigated. Results: A total of 392 DEGs, 2667 DMRs, and 464 DMIs were found between the two groups, and a functional interaction network of DEGs was established. Then, 28 potential key genes were identified, which were oppositely regulated in preeclampsia regarding expression and methylation. Eight of the potential key genes had DMIs, among which ITGA5 interacted with FN1 and FOS. The 3 DEGs were up-regulated, and their DMIs were hypomethylated. Conclusion: FN1, FOS, and ITGA5 might promote the development of preeclampsia via modulating differentiation/apoptosis/invasion of human extravillous trophoblasts, as well as focal adhesion, VEGFR3 signaling, β1 integrin cell surface interactions, α9β1/α4β1 integrin signaling, AP-1/ATF-2/HIF-1α transcription factor networks, and Fc-epsilon receptor I signaling in mast cells.